2015
DOI: 10.1186/1476-069x-14-14
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous air pollutants and breast cancer risk in California teachers: a cohort study

Abstract: BackgroundStudies suggest that higher breast cancer rates in urban areas persist after accounting for the prevalence of known risk factors, leading to speculation that urban environmental exposures, such as air pollution, may play a role in the etiology of breast cancer. Combining modeled ambient air concentrations with data from a large prospective cohort of California women with over 15 years of follow-up, we examined the relationship between breast cancer incidence and modeled concentrations of air pollutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 37 publications
0
41
1
9
Order By: Relevance
“…Human and laboratory studies have been conducted on the role of these 2 elements in preventing carcinogenesis process and tumor cell growth (19)(20)(21)(22). On the other hand, epidemiological studies have shown that differences in dietary habits or diet (23,24) and air pollution (25) can effect on risk of BC, in line with genetics (26). In Ku's study, it was suggested that change the vital elements in serum and tissue might be beneficial and considerable biomarkers in BC (27).…”
Section: Discussionmentioning
confidence: 94%
“…Human and laboratory studies have been conducted on the role of these 2 elements in preventing carcinogenesis process and tumor cell growth (19)(20)(21)(22). On the other hand, epidemiological studies have shown that differences in dietary habits or diet (23,24) and air pollution (25) can effect on risk of BC, in line with genetics (26). In Ku's study, it was suggested that change the vital elements in serum and tissue might be beneficial and considerable biomarkers in BC (27).…”
Section: Discussionmentioning
confidence: 94%
“…Research on the health effects of the air pollutant benzene has historically focused on occupationally-exposed men (IOM (Institute of Medicine) 2012). However, a study in New York did find an association among women who were likely to have moderate to high exposure based on job-exposure matrices (Petralia et al 1999) and an association was observed with ER-PR- tumors in the California Teacher’s Cohort study (Garcia et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The study found suggestive associations for NO 2 , and the US Sister Study found significantly higher risk of ER+/PR+ tumors with NO 2 exposure (112). The California Teachers Study found associations between ER+/PR+ tumors and some mammary gland carcinogens (44) and between ER−/PR− tumors and ambient benzene (44), cadmium, and arsenic (77). The Nurses' Health Study II did not find these associations (48), but the cohort was younger than that of the California Teachers Study.…”
Section: Air Pollution and Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 82%